Economic feasibility of intensive aquaculture integrated with irrigation system - Bag, Narayan; Moulick, Sanjib; Mal, Bimal Chandra (Indian Journal of Fisheries, 2014)
The Indian major carps (IMC) Catla catla, Labeo rohita, and Cirrhinus mrigala, were cultured at three different stocking densities viz., 20000 (St.D-2.0), 35000 and 50000 (St.D-5.0) fingerlings ha-1 for a period of 300 days with suitable management practices. The wastewater from the ponds was judiciously reused to irrigate crops. A comparative evaluation of economic feasibility (St.D-3.5) was made between (i) the actual study conducted within the irrigation system (WIS) and (ii) a hypothetical case of aquaculture performed alone (OIS). Significantly higher net present value (NPV) and internal rate of return (IRR) and lower value of payback period were estimated in WIS compared to OIS for all three stocking densities (p<0.05). Significantly higher values of NPV of ` 56,12,161/- and IRR of 82.86% were obtained in WIS compared to the NPV of ` 47,81,635/- and the IRR of 69.55% in OIS for the treatment, St.D-5.0. The results strongly established the effectiveness of aquaculture conducted within an irrigation system, from an economic point of view.